ANALISIS KONDISI SOSIAL EKONOMI MASYARAKAT DI SEKITAR KAWASAN USAHA ROTAN UD. MUDA KARYA DI DESA WANTULASI KECAMATAN WAKORUMBA UTARA KABUPATEN BUTON UTARA - Devi Indrayana; Fajar Saranani; Nur Asizah (JEP (Jurnal Ekonomi Pembangunan), 2021)
The purpose of this research is to analyze the socio-economic conditions of the community in the UD rattan business area. Muda by Wantulasi Village, Wakorumba Utara District, Buton utara Regency . The research method used is field research by conducting observation, interviews, and documentation.  This can be seen from the education of the respondents, where out of 23 respondents, 6 respondents or around 26.08% completed their formal education at the high school level, then seen from the health condition it can be categorized as good, which can be seen from the type of treatment of respondents who seek treatment at the health center as many as 15 people. or about 65.21%, then seen in terms of the number of family members, indirectly with the presence of UD. Muda Karya affects the ability of each family to bear the burdens of their respective families due to the existence of UD. Muda Karya affects livelihoods and income in every family. The average number of dependents in the family is 3-4 people, 11 respondents or 47.82%. Then from an economic point of view it is classified as moderate where the average income of respondents of month Rp. 1.844.348